Worlds apart? A scoping review addressing different stakeholder perspectives on barriers to family involvement in the care for persons with severe mental illness - Elleke Landeweer; Bert Molewijk; Marit Helene Hem; Reidar Pedersen (BMC, 2017)
Abstract Background Empirical evidence shows that family involvement (FI) can play a pivotal role in the coping and recovery of persons with severe mental illness (SMI). Nevertheless, various studies demonstrate that FI in mental healthcare services is often not (sufficiently) realized. In order to develop more insights, this scoping review gives an overview of how various stakeholders conceptualize, perceive and experience barriers to FI. Central questions are: 1) What are the main barriers to FI reported by the different key stakeholders (i.e. the persons with SMI, their families and the professionals, and 2) What are the differences and similarities between the various stakeholders' perspectives on these barriers. Methods A systematic search into primary studies regarding FI was conducted in four databases: Medline/Pubmed, Cinahl, PsychInfo and Web of Knowledge with the use of a PICO scheme. Thematic analysis focused on stakeholder perspectives (i.e. which stakeholder group reports the barrier) and types of barriers (i.e. which types of barriers are addressed). Results Thirty three studies were included. The main barriers reported by the stakeholder groups reveal important similarities and differences between the stakeholder groups and were related to: 1) the person with SMI, 2) the family, 3) the professionals, 4) the organization of care and 5) the culture-paradigm. Discussion Our stakeholder approach elicits the different stakeholders' concepts, presuppositions and experiences of barriers to FI, and gives fundamental insights on how to deal with barriers to FI. The stakeholders differing interpretations and perceptions of the barriers related to FI is closely related to the inherent complexity involved in FI in itself. In order to deal better with these barriers, openly discussing and reflecting upon each other's normative understandings of barriers is needed. Conclusions Differences in perceptions of barriers to FI can itself be a barrier. To deal with barriers to FI, a dialogical approach on how the different stakeholders perceive and value FI and its barriers is required. Methods such as moral case deliberation or systematic ethics reflections can be useful.